2012
DOI: 10.4401/ag-6146
|View full text |Cite
|
Sign up to set email alerts
|

Quick regional centroid moment tensor solutions for the Emilia 2012 (northern Italy) seismic sequence

Abstract: <p>In May 2012, a seismic sequence struck the Emilia region (northern Italy). The mainshock, of Ml 5.9, occurred on May 20, 2012, at 02:03 UTC. This was preceded by a smaller Ml 4.1 foreshock some hours before (23:13 UTC on May 19, 2012) and followed by more than 2,500 earthquakes in the magnitude range from Ml 0.7 to 5.2. In addition, on May 29, 2012, three further strong earthquakes occurred, all with magnitude Ml ≥5.2: a Ml 5.8 earthquake in the morning (07:00 UTC), followed by two events within just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…The seismic sequence involved an area that extended in an E-W direction for more than 50 km, and included seven M L ≥5.0 events and more than 2,300 M L >1.5 events (http://iside.rm.ingv.it). The focal mechanisms of the main events [Pondrelli et al 2012, Scognamiglio et al 2012 consistently showed compressional kinematics with E-W oriented reverse nodal planes.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The seismic sequence involved an area that extended in an E-W direction for more than 50 km, and included seven M L ≥5.0 events and more than 2,300 M L >1.5 events (http://iside.rm.ingv.it). The focal mechanisms of the main events [Pondrelli et al 2012, Scognamiglio et al 2012 consistently showed compressional kinematics with E-W oriented reverse nodal planes.…”
Section: Introductionmentioning
confidence: 88%
“…109˚ striking fault plane, with a thrusting mechanisms (rake, ca. 89˚) [Scognamiglio et al 2012] and Quick Regional Centroid Moment Tensor [Pondrelli et al 2012] focal solutions, respectively. The seismicity (from http://iside.rm.ingv.it) and the topography are also shown in the profiles.…”
Section: Coseismic Displacement and Fault Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In May 2012, several medium-large earthquakes impacted on a wide portion of the alluvial plain of northern Italy (Figure 1), belonging to the Lombardy, Veneto and Emilia-Romagna regions. The strongest earth-quake (M L 5.9) occurred close to Finale Emilia, while the second largest one (M L 5.8) took place near Mirandola [Pondrelli et al 2012]. The causative faults belong to the Ferrara Arc thrust system [Bonini et al 2014, DISS Working Group 2015, forming the external portion of the Apennines Chain (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The thrust faulting focal mechanisms of the main shocks and the strongest aftershocks show fault planes with E-W, ENE-WSW, and WNW-ESE orientations [Pondrelli et al 2012, Scognamiglio et al 2012, compatible with the approximately N-S direction of the compression in the area [Montone et al 2012].…”
Section: Introductionmentioning
confidence: 87%